Validity of algorithm for estimating left sided filling pressures on echocardiography in a population referred for pulmonary arterial hypertension. (1st November 2017) - Leung, Eric C.; Swiston, John R.; AlAhmari, Leena; AlAhmari, Tasneem; Huckell, Victor F.; Brunner, Nathan W.
Abstract : The determination of LV filling pressure is integral to the diagnosis of pulmonary arterial hypertension (PAH). The American Society of Echocardiography (ASE) has devised algorithms for their estimation. We aimed to test these algorithms in a population referred for suspected PAH. In our retrospective study, we evaluated the accuracy of the ASE Algorithms compared to right heart catheterization done within three months, in patients seen during 2006–2014. All echocardiograms were classified as showing normal, elevated or indeterminate filling pressures. Those with indeterminate pressures were excluded. We evaluated the diagnostic properties of this algorithm to predict a pulmonary artery wedge pressure (PAWP) and left ventricular end diastolic pressure (LVEDP) >15 mmHg. A total of 94 patients were included. The ASE algorithms yielded indeterminate results in 50 (53.2%) patients. This occurred more commonly in older patients and patients with cardiovascular comorbidities. The algorithm had a high sensitivity for predicting an elevated PAWP at 89.5% (95% confidence interval [CI] = 66.9–98.7) and an elevated LVEDP at 100% (95% CI = 76.8–100). The algorithm had a negative predictive value of 81.8% and 100% for predicting an elevated PAWP (95% CI = 52.4–94.8) and LVEDP, respectively, but a poor positive predictive value. The ASE algorithm for predicting LV filling pressures often cannot be applied in populations with suspected PAH. When they are interpretable, they have a high negative predictive value for elevated PAWP and LVEDP. We recommend caution when using these algorithms in populations with suspected PAH.